Suppression of Pool Fire in a Large Enclosure with Water Mist. (September 2013) - Lal, Suresh; Gupta, Meenakshi; Kushari, A.; Kapoor, J.C.; Maji, S.
This paper reports the results of an experimental study of suppression of pool fires in enclosed spaces using water mist. The main objective of the present study is to understand the mechanisms responsible for the suppression of pool fires using water mists. Experiments were conducted in a large compartment with n-heptane pool fires of different heat release rates. The temperature variations in the compartment were measured using K-type thermocouples fixed at two locations. A multi gas analyzer was used to measure gas concentrations. The test results indicate that the water mist suppresses the diffusion flame in an enclosed space mainly through evaporating cooling and oxygen displacement by water vapors, resulting in inefficient combustion. The fire suppression time decreases with a decrease in droplet diameter. It is much easier to suppress a larger fire due to faster rates of evaporation of water droplets and therefore, the total mist requirement decreases with an increase in the fire size. The results of this study can find application in the design of water mist based fire fighting systems for indoor fires.